Alternative procedures for resolving international trade disputes (Numerus academy review, 2026)
The development of cross-border international trade operations and theinadequacy of national laws for settling disputes arising from them, constituted aninevitable necessity to search for a more specialized technical tool to resolve thesedisputes away from the national judiciary of the state, which is what the Algerian legislator tried to devote within the Civil and Administrative Procedures Law through theprovisions of commercial arbitration. International to ensure the settlement ofinternational trade disputes.Where this study aims to reveal the most effective solutions to resolve this type of disputes through arbitration to ensure the speed of their settlement in light of theirprivacy, as well as the scope of judicial intervention in that.